EFEKTIVITAS DISTRACTOR PADA TES PILIHAN GANDA UNTUK MENDETEKSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA - Yani, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The aim of this study is to determine the effectiveness of the distractor on multiple choice tests to detect the students’ errors and the types of errors students made in solving math problems. This research is a descriptive qualitative study which research subjects were students of class IX MTsN Model Banda Aceh that consisted of 36 students, then three students were selected as subjects to be interviewed about mastery and mistakes made when completing math problems. Data were collected through tests and interviews which validity was used to test the credibility of the data by means of triangulation. Data analysis consisted of the stages of data reduction, data presentation, and conclusion drawing. The results showed that: 1) A good distractor on multiple choice tests had been completed such as a description test question for each answer option chosen by the students was very effective for detecting students’ errors in solving mathematics problems, in which 17.1% of students incorrectly applied mathematical concepts , 3.7% of students made mistakes due to lack of accuracy or error, 1.2% of students misunderstood the problem, and 4.7% of students did not make a solution, but only guessed from the ten questions given. 2) Conceptual errors made by the three subjects (MAH, BSR, and PES) were errors in analyzing the combined area of space and errors in algebraic factorization. Errors in understanding and applying the difference formula were only done by the subject MAH, errors in determining the square root of a number were only done by the subject BSR, and errors in squaring a number were only done by the subject PES. While procedural errors due to lack of thoroughness or error in substituting a value were carried out by subject MAH and PES, errors due to the inability to manipulate steps to solve a problem were only carried out by the subject MAH, and errors in writing the final results were only done by the BSR subject.